A Development Of Charging System For Electric Vehicles - Pristisal Wibowo; Beni Satria; M. Erpandi Dalimunte; Alim Muflih (Sean Institute, 2024)
The increasing use of electric vehicles (EVs) requires adequate and efficient charging system infrastructure. One of the main things is the charging system for electric vehicles (EV) batteries. This study aims to develop a charging system infrastructure for EVs using a DC to DC converter. This study examines the design and implementation of a charging system with a DC to DC converter to transform DC voltage from the grid to a DC voltage that meets the needs of EV batteries. This system is designed to ensure safety, efficiency, and compatibility with various types of EVs. The system is also capable of producing voltages from 12 volts to more than 60 volts, which is sufficient to charge electric vehicle batteries. Correlation analysis simulations with MATLAB and experimental testing were conducted to evaluate the performance of the charging system. The results show that this system is capable of charging EV batteries safely and efficiently. This system is also compatible with various types of EVs and can be easily integrated with the electricity grid. The development of a charging system infrastructure with a DC to DC converter is expected to support widespread EV adoption and contribute to a sustainable energy transition.